The THE INFLUENCE OF JOB SATISFACTION AND WORK MOTIVATION ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) OF STUDENT EMPLOYEES IN SUBANG DISTRICT: Array - Faza Shidiq Ahyat; Sriwulan Anggraeni (STIESA Press, 2025)
This study aims to analyze the effect of job satisfaction and work motivation on Organizational Citizenship Behavior (OCB) in student employees in Subang Regency. The approach used is a quantitative approach with a survey method. The research sample amounted to 41 respondents selected using purposive sampling technique. Data were collected through structured questionnaires and analyzed using multiple linear regression. The results showed that job satisfaction and work motivation had a positive and significant effect on OCB both partially and simultaneously. The t test shows that job satisfaction has a significant effect on OCB with a significance value of 0.011, while work motivation also has a significant effect with a significance value of <0.001. Simultaneously, the F test produces a significance value <0.001, which means that the two variables together have a significant effect on OCB. The coefficient of determination (R²) value of 0.812 indicates that 81.2% of the variation in OCB behavior can be explained by job satisfaction and work motivation. This finding suggests that increasing job satisfaction and motivation can encourage the emergence of positive voluntary work behavior in student employees. Therefore, educational institutions and workplaces need to create a supportive work environment and appropriate motivation enhancement strategies to encourage productive and proactive behavior.